Strategi Aspek Lingkungan pada Usaha Bisnis Richeese Factory - Siti Afifah Salsabila; Tantri Arum; Siti Zahra Amelia Putri Nasution; Ananda Putri Ariyani; Cut Zahara Salidia Sabrina; Mutiah Khaira Sihotang (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
This study discusses the importance of environmental aspect strategy in sustainable business management with a case study on Richeese Factory business. This study aims to provide insight into how Richeese Factory can integrate environmental aspects into their business strategy, as well as the benefits and challenges that may be faced. Thus, it is hoped that Richeese Factory can contribute to environmental sustainability while still achieving their business goals. The method used is a qualitative method with a case study in the form of interviews and observations, so that efficient resource management, use of renewable energy, and recycling programs have been implemented by Richeese Factory to reduce their environmental footprint. However, the implementation of this strategy is not without challenges, such as high initial costs and the need to adapt to new technologies. However, there are many opportunities that can be utilized, such as increasing consumer demand for environmentally friendly products and incentives from the government